Surface water availability and agro-pastoral practices shape the human-wildlife interface at the edge of a protected area - Valls Fox, Hugo, author; Chamaillé-Jammes, Simon, author; de Garine-Wichatitsky, Michel, author; Perrotton, Arthur, author; Courbin, Nicolas, author; Miguel, Eve, author; Guerbois, Chloé, author; Caron, Alexandre, author; Loveridge, Andrew, author; Stapelkamp, Brent, author; Muzamba, Martin, author; Fritz, Hervé, author; et al. (Colorado State University. Libraries, 2016)
Spatial and temporal partitioning of key resources promotes species coexistence. On the edge of unfenced protected areas, livestock and wild herbivores share foraging and watering resources. We investigated whether effective resource partitioning was maintained in African savannas as surface water availability declined during the dry season. We quantified avoidance between African elephant (Loxodonta Africana), African buffalo (Syncerus caffer) and cattle (Bos taurus & indicus) at multiple scales using habitat selection models with GPS relocation data according to seasonal changes in surface water distribution on the eastern fringe of Hwange National Park, Zimbabwe. The range and duration of cattle incursions into the protected area varied seasonally by shifting from consistent selection of open habitats close to water pans during the rainy season to the less predictable selection of areas far away from the now dried up water pans at the end of the dry season. During the rainy and cold dry season, buffalo successfully avoid cattle at large (overlap<3%) and fine spatial scales. By the end of the dry season, buffalo herds, which are restricted to the vicinity of water, still avoid the boundary of the protected area but tolerate higher overlap with cattle (10%) and do not avoid them as strongly at fine scales. Elephant home-ranges overlap extensively with cattle (15-68%) throughout the year but elephant avoid cattle by staying away from the boundary during the day and getting closer to it at night. As the dry season advances, elephant bulls range closer to the boundary especially at night and may even make excursions into the communal land in their search of forage. Synthesis: Wild herbivores strongly avoid livestock and people at the boundary of a protected area as long as their foraging and drinking resources allow. In the advent of a drought, artificial water provisioning and cattle husbandry determine the level of avoidance and may be used to mitigate disease transmission and crop-raiding.
Surface water availability and cattle herding practices shape the human-wildlife interface at the edge of a protected area
Presented at the 9th international wildlife ranching symposium: wildlife - the key to prosperity for rural communities, held on 12-16 September 2016 at Hotel Safari & the Safari Court, Windhoek, Namibia in conjuction with the IUCN 2nd African Buffalo Symposium.